Optimized electroacupuncture treatment for female stress urinary incontinence: study protocol for a multi-center randomized controlled trial - Liu, Lumin; Chen, Bingli; Si, Xiaohui; Hou, Wenguang; Fan, Qian; Li, Xu; Li, Juanjuan; Ming, Shuren; Yin, Ping; Chen, Yuelai (Frontiers in Psychiatry, 2023)
Background : Stress urinary incontinence (SUI) is a common condition that can severely affect women's life quality. Electroacupuncture (EA) has been proved to be an optional treatment for SUI, but the tolerance of EA becomes a factor affecting efficiency, which should not be ignored and needs to be solved urgently. The purpose of this study is to find out whether the use of alternating acupoints combination can solve this problem or not and provide an optimization of EA treatment for female SUI. Methods: This multi-center randomized controlled trial will enroll 360 patients with SUI. They will be randomly assigned to one of the three groups - sacral acupoints group (Sacral group), abdominal acupoints group (Abdominal group), or alternating acupoints group (Alternating group) - at a 1:1:1 ratio. The patients will receive 18 sessions of EA treatment and will be followed up for 48 weeks after the treatment. The primary outcome measure of the study is the change of urine leakage at week 6. The secondary outcomes include the incontinence episode frequency (IEF), International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF), severity of SUI, patient self-evaluation of therapeutic effects, weekly usage of urine pads, ultrasonography of pelvic floor, specialty therapies for SUI, evaluation of discomfort during EA treatment, patient acceptability evaluation and adverse events related to intervention. Discussion: This trial is specifically designed to offer an optimized EA treatment for female SUI, aiming to enhance their quality of life. Trial registration : The trial is registered on ClinicalTrials.gov (ID:NCT05635669). Register date: 12/11/2022, https://clinicaltrials.gov/ct2/show/NCT05635669.